Efficacy of rotavirus vaccines in Indonesia: A review of genotype distribution and impact - Aman, Abu T.; Patriani, Afifah; Mawarti, Yuli (Narra Sains Indonesia, 2025)
Rotavirus remains the leading cause of diarrhea among children under five years of age, with an incidence of 31.1–90.9% in Indonesia. Initially, a rotavirus vaccination program was introduced in several provinces of Indonesia in 2022, which would be conducted nationally. This review provides information on the rotavirus genotype distribution in Indonesia, efficacy and effectiveness data of the rotavirus vaccine, and an update on the status of rotavirus vaccine implementation worldwide. The results show a varied distribution of G and P genotypes from 1978 to 2018, with G1–G3, G9, P[4], P[6], and P[8] as the prevalent genotypes, followed by a small proportion of G4, P[9], P[10], and P[11]. Three rotavirus vaccines, which are prequalified by the World Health Organization (WHO) and available in Indonesia, showed an efficacy of 17.6–76.9% in high-mortality countries. The Indonesian government procured ROTAVAC with a G9P[11] genotype for the national immunization program, which showed 31.3–69.1% protective efficacy against severe gastroenteritis caused by other strains. This review suggested that the decision to choose the rotavirus vaccine for the national program should take into account the country’s prevalent circulating genotype and the vaccine’s efficacy against severe diarrhea. The use of a pentavalent rotavirus vaccine with high efficacy in high-mortality countries can be regarded as the prime choice for the program. Another alternative is the rotavirus vaccine, which showed efficacy data in multiple high-mortality countries. In addition, regular surveillance of the rotavirus genotypes and the clinical manifestations of diarrhea are necessary to design vaccination strategies in Indonesia.